The importance of humanization in urgencies and emergencies (Research, Society and Development, 2023)
Introduction: The National Humanization Policy (NHP) was instituted in 2003, as a way to improve the care provided to users and have a more sensitized and focused look at the individualities and complexity of care among users, through the reception and risk classification in emergency care. Objective: To verify in the databases the most recent publications on the positive impacts of humanization within urgency and emergency. Methodology: This is an integrative literature review elaborated by the following stages: choice of theme and elaboration of the research problem. Definition of criteria adopted for inclusion and exclusion for the sample; definition of key words; display of information through an instrument such as table or chart; data analysis; explanation of the results; evidence the results found. Results: After detailed evaluation of the articles, 10 articles were selected that answered the research's guide line and offered significant subjects for the development of the research. The strategies and difficulties encountered by health professionals were exposed to put into practice in the face of the emergency scenario. Conclusion: Welcoming was one of the most used strategies within the humanization policy evidenced in the studies analyzed, because it provides a moment between professional and user providing a dialogue and evaluating the complaints and anxieties that come from the patient.